2014
DOI: 10.1007/s12070-014-0718-2
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Molsidomine on the Cisplatin-Induced Ototoxicity

Abstract: This experimental study was designed to investigate the protective effects of molsidomine (MOL) on against cisplatin-induced ototoxicity (CIO). To examine this effect, distortion product otoacoustic emissions (DPOAEs) measurements and serum levels of oxidative and antioxidant status [including malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), glutathione peroxidase (GPX), total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI)] were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Diabetes produces a significant oxidative damage in sciatic nerve as indicated by an increase in lipid peroxidation and nitric oxide concentration as well as depletion of antioxidant enzymes. 27 Previous experimentations have shown that the oxidative stress induced by diabetes causes damage to protein, lipid, DNA and also causes damages myelin sheath surrounding the nerve. In the present study, increase in MDA levels and depletion in reduced glutathione was seen in sciatic nerve homogenate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes produces a significant oxidative damage in sciatic nerve as indicated by an increase in lipid peroxidation and nitric oxide concentration as well as depletion of antioxidant enzymes. 27 Previous experimentations have shown that the oxidative stress induced by diabetes causes damage to protein, lipid, DNA and also causes damages myelin sheath surrounding the nerve. In the present study, increase in MDA levels and depletion in reduced glutathione was seen in sciatic nerve homogenate.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes causes a significant oxidative damage in the sciatic nerve as indicated by an increase in lipid peroxidation and nitric oxide concentration, as well as depletion of antioxidant enzymes. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical applications of MLS in the field of cardiology are well established, especially relating to the symptomatic treatment of angina [6][7][8][9]. Apart from these properties, it is also well established that MLS exerts antioxidant and anti-inflammatory effects [32][33][34].…”
Section: Discussionmentioning
confidence: 99%